VD_FINDINFO HC / 2011 / 106 vom 8. Dezember 2010 - VD Tribunal cantonal (2010)
ABUS DE DROIT, BAIL À LOYER, FORMULE OFFICIELLE, ENRICHISSEMENT ILLÉGITIME | 142 CO, 269d CO, 270 CO, 67 CO, 452 CPC, 456a CPC, 471 al. 3 CPC, 13 LTB